EMPLOYEE PERFORMANCE REVIEWED FROM KNOWLEDGE MANAGEMENT, ATTITUDE AND TRAINING AT SAHID JAYA HOTEL SOLO - Syahidin, Rizal Fadhilah; Sudarwati, Sudarwati; Damayanti, Ratna (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to test the influence of Knowledge Management, Attitude and Training on employee performance at Sahid Jaya Hotel Solo. The population in this study was 75 employees. This study used census sampling techniques because the sample studied was the entirety of the existing population or called the census, based on policies during the pandemic, then the employees who attended as many as 45 employees. In this study, researchers took a sample of 45 employees. This research is quantitative research. The data analysis techniques used for this study used multiple liner regression. Based on the results of hypothetical tests, especially the F test, it was found that knowledge management, attitude, and training simultaneously have a positive and significant influence on employee performance. T test results show that Knowledge Management has a positive and significant effect on employee performance, Attitude has no effect on employee performance, Training has a positive and significant effect on employee performance.